Visualizing Potential-Induced Pitting Corrosion of Ultrathin Single-Crystalline IrO2(110) Films on RuO2(110)/Ru(0001) under Electrochemical Water Splitting Conditions - Weber, Tim; Ortmann, Till; Escalera-López, Daniel; Abb, Marcel J.S.; Mogwitz, Boris; Cherevko, Serhiy; Rohnke, Marcus; Over, Herbert (ChemCatChem, 2019)
Sophisticated IrO2(110)-RuO2(110)/Ru(0001) model electrodes are employed in the oxygen evolution reaction (OER) under acidic conditions. The potential-induced pitting corrosion of such electrodes is confirmed by a variety of experimental techniques, including scanning electron microscopy (SEM), time-of-flight secondary ion mass spectrometry (ToF-SIMS), and operando scanning flow cell-inductively coupled plasma mass spectrometry (SFC-ICP-MS). The structure of the pits is reminiscent of a cylinder (evidenced by focused ion beam scanning electron microscopy: FIB-SEM), where the inner surface of the pits is covered by hydrous RuO2 (cyclic voltammetry, ToF-SIMS) that is formed by electrochemical oxidation of the metallic Ru(0001) substrate. The time evolution of the corrosion process at a fixed electrode potential (1.48 V vs. SHE) is followed via cyclic voltammetry and SEM. The passivating IrO2(110) layer results in an “induction period” for the pit growth that is followed by rapid corrosion of the RuO2(110)/Ru(0001) substrate. The observed narrow and time-independent size distribution relative to the mean size of the pits is attributed to a sluggish removal of the corrosion products by diffusion across the cracks of the pits covering IrO2 layer, leading to steady state corrosion during a total polarization time of 20 to 60 minutes.
CRIS-Team Scopus Importer:2019-12-17
Keywords: anodic corrosion; electron microscopy; mass spectrometry; oxygen evolution reaction (OER); single-crystalline electrodes